2021
DOI: 10.3390/genes12020177
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA FENDRR: Gene Structure, Expression, and Biological Relevance

Abstract: The FOXF1 Adjacent Noncoding Developmental Regulatory RNA (Fendrr) plays an important role in the control of gene expression in mammals. It is transcribed in the opposite direction to the neighboring Foxf1 gene with which it shares a region containing promoters. In humans, FENDRR is located on chromosome 16q24.1, and is positively regulated both by the FOXF1 distant lung-specific cis-acting enhancer and by trans-acting FOXF1. Fendrr has been shown to function as a competing endogenous RNA, sponging microRNAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 82 publications
(121 reference statements)
0
12
0
Order By: Relevance
“…Emerging evidence found that lncRNAs played the role of "sponges" of miRNAs in order to take part in various processes of the cell [15][16][17]. As a kind of small RNA, miRNA also has an important function in septic AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence found that lncRNAs played the role of "sponges" of miRNAs in order to take part in various processes of the cell [15][16][17]. As a kind of small RNA, miRNA also has an important function in septic AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The DEirlncRNAs used to construct the signature in this study play critical roles in a variety of tumors. Dysregulation of FENDRR expression is associated with tumorigenesis, resistance to chemotherapy, fibrosis, and inflammatory diseases ( Szafranski and Stankiewicz, 2021 ). In colorectal cancer, Yin et al (2019) revealed that FENDRR could inhibit tumor aggressiveness by regulating the miR-18a-5p/ING4 axis.…”
Section: Discussionmentioning
confidence: 99%
“…According to existing research, the nuclear location of lncRNA modulates chromatin organization, RNA processing and transcription. [35][36][37] LncRNAs can negatively or positively affect the expression of target genes. For example, lncRNA PDPK2P can as a factor interact with proteins.…”
Section: Discussionmentioning
confidence: 99%